Development of Controlled-Release Carbamide Peroxide Loaded Nanoemulgel for Tooth Bleaching: In Vitro and Ex Vivo Studies - Siriporn Okonogi; Adchareeya Kaewpinta; Sakornrat Khongkhunthian; Pisaisit Chaijareenont (MDPI AG, 2021)
Burst release of carbamide peroxide (CP) from traditional hydrogels causes severe inflammation to periodontal tissues. The present study explores the development of a novel CP nanoemulgel (CP-NG), an oil-in-water nanoemulsion-based gel in which CP was loaded with a view to controlling CP release. CP solid dispersions were prepared, using white soft paraffin or polyvinylpyrrolidone-white soft paraffin mixture as a carrier, prior to formulating nanoemulsions. It was found that carrier type and the ratio of CP to carrier affected drug crystallinity. Nanoemulsions formulated from the optimized CP solid dispersions were used to prepare CP-NG. It was found that the ratio of drug to carrier in CP solid dispersions affected the particle size and zeta potential of the nanoemulsions as well as drug release behavior and tooth bleaching efficacy of CP-NG. Drug release from CP-NG followed a first-order kinetic reaction and the release mechanism was an anomalous transport. Drug release rate decreased with an increase in solid dispersion carriers. CP-NG obtained from the solid dispersion with a 1:1 ratio of CP to the polymer mixture is suitable for sustaining drug release with high tooth bleaching efficacy and without reduction of enamel microhardness. The developed CP-NG is a promising potential tooth bleaching formulation.